Applying the Kaizen in Africa A New Avenue for Industrial Development - Otsuka, Keijiro; Jin, Kimiaki; Sonobe, Tetsushi (Springer Nature, 2018)
At present, how to develop industries is a burning issue in Africa, where population growth remains high and economic development has thus far failed to provide sufficient jobs for many, especially young people and women. The creation of productive jobs through industrial development ought to be a central issue in steering economic activity across the continent. The authors of this book, consisting of two development economists and five practitioners, argue that the adoption of Kaizen management practices, which originated in Japan and have become widely used by manufacturers in advanced and emerging economies, is decisively the most effective first step for industrial development in Africa. This open access book discusses what Kaizen management is, why it is applicable to Africa, and why it can provide Africa with a springboard for sustainable economic growth and employment generation.